Developing Multiple Intelligences Theory to Improve the Effectiveness of Adaptive Learning in MTs Hidayatus Shibyan Students - Ma'rifatunni'mah, Ulil; Isriyah, Mudafiatun; Mawaddati, Ika Romika (IAIN Kudus, 2026)
Developing Multiple Intelligences Theory to Improve the Effectiveness of Adaptive Learning in MTs Hidayatus Shibyan Students. This research aims to improve students' focus in the learning process thru the development and implementation of an adaptive learning model based on Multiple Intelligences theory. This research uses a development research type (Research and Development / R&D) with the goal of developing a new product to improve the effectiveness of adaptive learning in students. The research procedure includes product development, product validation, and product testing. The study population consisted of 78 students from MTs Hidayatus Shibyan, with a sample of 10 students from class IX. The research instruments included expert validation assessment sheets (content experts and language experts). Data analysis yielded expert validation test scores. The validation test results showed that the development of Multiple Intelligences theory to improve the effectiveness of adaptive learning was feasible for use with students. The content expert validation test scored 80 (very good), and the language/media expert validation test scored 78 (good), resulting in a final average score of 79.00 (good). A